Predominance and first complete genomic characterization of canine parvovirus 2b in Turkey - Abayli, Hasan; Aslan, Oznur; Tumer, Kenan Cagri; Can-Sahna, Kezban; Tonbak, Sukru (Springer Wien, 2022)
Viral enteritis is a significant threat to domestic dogs. The two primary pathogens that cause viral enteritis in dogs are canine coronavirus (CCoV) and canine parvovirus (CPV). In this study, we investigated the occurrence of CPV-2, CCoV, and canine circovirus coinfection by characterizing circulating subtypes of CPV-2 in faecal samples from symptomatic dogs admitted to veterinary clinics located in Ankara, Elazig, Kayseri, and Kocaeli provinces of Turkey, between 2019 and 2022. Virus detection by PCR and RT-PCR revealed that CPV-2 was present in 48 (77.4%) samples, and no other agents were detected. Based on the occurrence of the codon GAT at positions 1276 to 1278 (coding for aspartate at residue 426) of VP2, all CPV-2 isolates were confirmed to be of the CPV-2b subtype. The complete genome sequences of two CPV-2b isolates showed a high degree of similarity to and phylogenetic clustering with Australian and East Asian strains/isolates. The predominant CPV strain circulating in the three different regions of Turkey was found to be a CPV-2b strain containing the amino acid substitutions at Y324I and T440A, which commonly contribute to immune escape. This is the first report of complete genomic analysis of CPV-2 isolates circulating in symptomatic domestic dogs in Turkey. The evolution of CPV-2 has raised questions about the efficacy of current vaccination regimes and highlights the importance of monitoring the emergence and spread of new CPV-2 variants.
Keywords: Molecular Characterization; Vp2 Gene; Phylogenetic Analysis; Sequence-Analysis; Host-Range; Dogs; Evolution; Type-2; Strains; Infection